Grassroots Governance and Judicial Administration from the Perspective of Five-Governance Integration: Multi-Collaborative Governance Logic and Practical Path - Li, Zhongmei (Journal of Theory and Practice in Humanities and Social Sciences, 2025)
This study is based on the goal of modernizing the national governance system. It takes the "five-governance integration" of politics, moral governance, legal governance, autonomy, and intelligent governance as the analytical framework, and systematically explores the interaction mechanism between judicial administrative functions such as people's mediation, community corrections, grassroots legal services, and lawyer management and grassroots governance. The study found that the integration of the five governances has formed synergistic effects in dispute resolution, transformation of special groups, legal communication, professional services and other fields through value integration and tool innovation: People's mediation resolves grassroots conflicts with the model of "rule of law framework + moral governance + autonomous participation + intelligent governance technology + political guidance" (such as a case of property dispute mediation in a community in Shanghai); community correction promotes the re-socialization of special groups through the path of "rule of law enforcement + moral governance education + autonomous integration + intelligent governance precision + political security" (such as a case of psychological intervention for community correction subjects in Zhejiang); grassroots legal services support grassroots governance with the system of "rule of law communication + autonomous empowerment + moral governance penetration + intelligent governance innovation + political tasks" (such as a case of legalization revision of village rules and regulations in Shaanxi); lawyer management improves governance professionalism through the mechanism of "rule of law norms + autonomous guidance + moral governance public welfare + intelligent governance collaboration + political responsibility" (such as a case of a lawyer team in Beijing participating in grassroots legislative consultation). This study provides a theoretical framework and empirical reference for understanding the functions of judicial administration and innovating grassroots governance models, and helps the grassroots practice of national governance modernization.